2015
DOI: 10.4197/met.26-2.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air Pollution on some Biochemical Parameters of Leaves of Three Tree Species Growing in the Industrial Area in Jeddah, Saudi Arabia

Abstract: The effect of industrial emissions on the levels of certain biochemical measurements in leaves of Camphor (Cinnamomum camphora), Henna (Lawsonia inermis), and Bougainvillea (Bougainvillea spectabilis) trees growing in the industrial zone in Jeddah -Saudi Arabia and Hada Al-Shame area (control) was done. Overall results showed that the content of chlorophyll a and b, total chlorophyll, carotenoids and protein in the plant leaf of the trees growing in the industrial zone were less comparing with the leaves of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The leaf area of Cinnamomum camphora (L.) Nees & Eberm., Lawsonia inermis L. and Bougainvillea spectabilis Willd. was decreased significantly in the industrial zone compared with the control area (Saudi Arabia) (Shaheen et al 2016). Areington et al (2015) showed that the leaf area of plants that had the closest distances to pollutants had a significant decrease compared to plants located farther away.…”
Section: Resultsmentioning
confidence: 96%
“…The leaf area of Cinnamomum camphora (L.) Nees & Eberm., Lawsonia inermis L. and Bougainvillea spectabilis Willd. was decreased significantly in the industrial zone compared with the control area (Saudi Arabia) (Shaheen et al 2016). Areington et al (2015) showed that the leaf area of plants that had the closest distances to pollutants had a significant decrease compared to plants located farther away.…”
Section: Resultsmentioning
confidence: 96%
“…Which factor that occurs on the road side causes the prolongation of the tracheid lengths should be investigated with further studies. The determination of air pollution is made with some studies on the trees on the roadside (Shaheen et al 2016, Wuyts et al 2018. Some studies reported that Mn, Fe, Zn, Cu, Ni, Co, Pb, Ti, V, Cr, As, Zr, Mo, Se, Cd, Pt metals were detected in tree leaves and outer surfaces of trees implanted near the road (Krupnova et al 2021, Ram et al 2015.…”
Section: Morphologic Analysis Resultsmentioning
confidence: 99%